Preparation of continuous nanofiber core-spun yarn by a novel covering method. (15th December 2016) - Liu, Cheng-Kun; He, Hai-Jun; Sun, Run-Jun; Feng, Yan; Wang, Qiu-shi
Abstract: A novel covering method to fabricate nanofiber core-spun yarn has been developed. Effects of span distance and rotation speed of disks on morphology, covering effect, abrasion resistance, wicking property, and mechanical property were mainly discussed in this investigation. Results showed that span distance had a significant effect on covering effect, and nanofiber core-spun yarn with a perfect covering effect could be prepared at the span distance of 2 cm with covering rate and abrasion growth rate of 30% and 142.3%, respectively. Alignment direction of nanofibers on the surface of nanofiber core-spun yarn was affected by rotation speed of disks, and would lead to the changes of wicking property and mechanical property. When the rotation speed of disks was 200 rpm, wicking property of nanofiber core-spun yarn was relatively better with the wicking effect of 7.6 cm. Breaking strength was decreased first and then increased with the increase of rotation speed. Graphical abstract: Highlights: A novel covering method to fabricate nanofiber core-spun yarn through electrospinning has been developed. A conventional yarn is placed between two parallel aluminum flakes to twist aligned nanofibers on the surface of core yarn. Most nanofibers were aligned on the surface of core yarn, and diameter of nanofibers was also relatively uniform. Wicking property of nanofiber core-spun yarn decreased with increase of rotation speed. Breaking strength was decreased first and then increased with the increase of rotation speed.